Machinery of state control: History of cinema censor board in Nepal - Maharjan, Harsha Man (Bodhi: An Interdisciplinary Journal, 2012)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5818 Bodhi 2010 4(1): 168-190